Two new species of the genera Leiophron Nees and Paroligoneurus Muesebeck (Hymenoptera: Braconidae) from northern India - Gupta, Ankita; van Achterberg, Cornelis; Pattar, Rohit; Navik, Omprakash; Mahendiran, G. (Zootaxa, 2022)
Two new species of parasitoid wasps, Leiophron indefinita Gupta & van Achterberg sp. nov. (Braconidae, Euphorinae) and Paroligoneurus indicus Gupta & van Achterberg sp. nov. (Braconidae, Ichneutinae) are described and illustrated from northern India.